Post-pleistocene colonisation rather than the contemporary environment has most influenced the current population structure of Scottish Atlantic salmon (Salmo salar) - Finn Cowell; Oscar E. Gaggiotti; Eef Cauwelier (PLoS ONE, 2025)
Genetic structuring in populations is the result of both historical and contemporary environmental factors driving genetic drift, natural selection and gene flow, as well as purely genetic factors, such as mutation and recombination. In Atlantic salmon (Salmo salar), re-colonisation of rivers after the last Ice Age was shown to be an important factor in shaping contemporary population structure, though the observed structure was more complex than was predicted through founder effects. Thus, other, perhaps more contemporary factors may also play a role. Here, we investigated the influence of the time since deglaciation, distance to the sea, population connectivity, temperature, water quality, waterbody modifications, and environmental protections on spatial structuring of genetic diversity, based on microsatellite data (33 loci) collected from 48 Scottish S. salar populations. The results confirmed that recently deglaciated areas are less genetically diverse and more differentiated. Modified waterbodies also exhibit less genetic diversity and greater differentiation, although this effect differs between rivers draining on the east and west coasts of Scotland. Distance to the sea also had a non-negligible effect, while the other considered factors did not have a significant effect.